Sintesis dan Karakteristik Membran Komposit Kitosan-Silika Untuk Pengolahan Limbah Cair Hotel: Variasi komposisi Kitosan-Silika - Baktiar Simaremare; Jhon Armedi Pinem; Syarfi Daud (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
The membrane is a selective and semipermeable layer that is between two phases, namely the feed phase and the permeate phase. Membrane synthesis using chitosansilica with phase inversion method. The purpose of this research were to make membranes of chitosan-silica for hotel waste water treatment with 2,5:2,5, 2,5:3, 2,5:3,5, 3:2,5, 3:3, 3:3,5, 3,5:2,5, 3,5:3, 3,5:3,5, 4:2,5, 4:3, dan 4:3,5 gram chitosansilika. This research produced porous membrane. The characterization membranes analysis were SEM analysis, tensile strength, flux and rejection. Tensile strength analysis showed that membrane with the highest tensile strenghth was 52,235 Mpa for membrane with 4:3,5 gram composition of chitosan-silika. Based on Flux and rejection results showed that membrane with 3:3,5 gram composition of chitosan-silika was the most effective performance with the flux 21,98 L/m2.h and rejection elimination of BOD was 54,32%, COD was 72,44% and TSS was 84,32%. Keywords : flux, membrane, rejection, ultrafiltration